Psychosocial Aspects of Erickson Model on Toileting Behavior For Toddler Ages: Case Study - Eriyono Budi Wijoyo; Mustikasari Mustikasari (Universitas Muhammadiyah Tangerang, 2019)
Introduction: Toddlers aged 1-3 years are children with psychosocial development stages between autonomy with shame and doubt so training is needed to control themselves, one of which is toilet training. Method: The process of writing this scientific article applied a case study approach with descriptive methods drawn from the writer's life and personal experience. To collect data in the form of articles, the writer used several databases such as PROQUEST, Science Direct, Google Search, and Scopus. The writer also used several search keywords, which are “Toodler Development”, “Erickson Theory”, “Toilet Training”, “Psychosocial Process”, by using boolean “AND”. Besides using keywords, the writer also used inclusion and exclusion criteria ranging from 2012-2017 published articles in Indonesian and English, and full text articles from reliable sources. From the aforementioned searches, thousands of articles were obtained and the writer analyzed and came up with the title “Psychosocial Aspects of Erickson Model in Toileting Behavior for Toddler Ages: Case Study”. Results and Discussion: The development of toddlers varies from one another. Toddlers can also carry out orders given from others to themselves. After entering the age of 24-30 months it is recommended that the children be trained in toileting behavior because at that age they can control themselves. Conclusion and suggestion:Children’s development in this case is still in line with Erikson's psychosocial development theory so that children are still within the psychosocial limits of health. Special attention is needed from parents to toddlers, especially related to their psychosocial development so that there is no delay and does not interfere with children's development at later stage. Keywords: Psychosocial, Erikson's Theory, Toddler, Toilet Training